The Implementation of Behavior-Based Management as an Attempt to Optimize Performance in Educational Institutions - Mochamad Iskarim (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
Educational institutions constitute strategic entities for realizing quality generations of a nation. However, in fact, it has been found that there have been lots of these institutions only focus on accepting a large number of students without maintaining the quality of their graduates. Additionally, nowadays, the institutions do not emphasize the enhancement of excellent services for their users so that it is deemed that the educational institutions have not demonstrated an impressive performance and a highly competitive atmosphere yet. Therefore, it is required to carry out advanced innovations for optimizing the performance of those educational institutions. It highlights that the optimization of their performances which are revealed by the whole civitas academica of the institutions tends to provide their services as well as realize quality generations. One of attempts to enhance the institutions’ performance is applying behavior-based management. This kind of management emphasizes the importance of positive behavior of the civitas academica in establishing educational services.